2011
DOI: 10.1182/blood-2009-10-248211
|View full text |Cite
|
Sign up to set email alerts
|

High STAT5 levels mediate imatinib resistance and indicate disease progression in chronic myeloid leukemia

Abstract: In BCR-ABL1 ؉ leukemia, drug resistance is often associated with up-regulation of BCR-ABL1 or multidrug transporters as well as BCR-ABL1 mutations. Here we show that the expression level of the transcription factor STAT5 is another parameter that determines the sensitivity of BCR-ABL1 ؉ cells against tyrosine kinase inhibitors (TKIs), such as imatinib, nilotinib, or dasatinib. Abelson-transformed cells, expressing high levels of STAT5, were found to be significantly less sensitive to TKI-induced apoptosis in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(142 citation statements)
references
References 52 publications
(84 reference statements)
12
125
1
1
Order By: Relevance
“…8 Moreover, during disease progression, the levels of STAT5 mRNA and protein increase, and STAT5 production and activation is triggered not only by BCR-ABL1 or mutant KIT, but also by other pro-oncogenic pathways relevant to disease progression and resistance. 9 Taken together, these observations strongly suggest that STAT5 and AKT are key drivers in drug-resistant CML and SM, and thus represent potential therapeutic targets. Small molecules targeting STAT5 or AKT may indeed be effective in these malignancies, especially in TKIs-resistant patients.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…8 Moreover, during disease progression, the levels of STAT5 mRNA and protein increase, and STAT5 production and activation is triggered not only by BCR-ABL1 or mutant KIT, but also by other pro-oncogenic pathways relevant to disease progression and resistance. 9 Taken together, these observations strongly suggest that STAT5 and AKT are key drivers in drug-resistant CML and SM, and thus represent potential therapeutic targets. Small molecules targeting STAT5 or AKT may indeed be effective in these malignancies, especially in TKIs-resistant patients.…”
Section: Introductionmentioning
confidence: 88%
“…9,48 However, mutations in the kinase domain of BCR-ABL1 are thought to be a primary cause of resistance in patients with CML, seen in up to 40-60% of cases of secondary resistance.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Mitogen-activated protein kinase, phosphoinositide 3-kinase, and JAK-STAT signaling are known to be involved in BCR-ABL-independent TKI resistance and represent targeting opportunities in CML (38). For example, STAT5 was shown to mediate imatinib resistance and was upregulated in leukemic cells from imatinib-resistant patients (39). Similarly, CML cell lines cultured with HS5 stromal cells were protected from imatinib-induced apoptosis by STAT3 upregulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that STAT5 regulated the sensitivity of cancer cells to chemotherapy. Researchers found that high STAT5 levels mediate imatinib resistance in chronic myeloid leukemia (CML) (25); inhibition of STAT5 by siRNA significantly reduced the activities of multi-drug resistant protein and enhanced the sensitivity of CML cells to imatinib (26). Research on squamous cell carcinoma of the head and neck demonstrated that STAT5 activation was associated with resistance to cisplatinmediated apoptosis and growth inhibition induced by the epidermal growth factor receptor tyrosine kinase inhibitor, such as erlotinib (27).…”
Section: Discussionmentioning
confidence: 99%